Omen and Anti-omen: The Rabbinic Hagiography of the Scapegoat's Scarlet Ribbon - Balberg, Mirah (Archiv für Religionsgeschichte, 2016)
This article proposes that the place and meaning of various objects among religious communities can be explored in terms of "hagiography," that is, through the narratives constructed around sacred objects sometimes long after their physical disappearance. It takes as its point of departure the assumption that in the same way that written accounts of saints' lives disclose more about the authors of these accounts than about the protagonists, so narratives regarding "things" reveal the concerns and debates of their authors, and in particular their concerns about materiality and divine presence within physical objects. The article explores the rabbinic narratives concerning the scarlet ribbon tied to the scapegoat of the Day of Atonement, its function and its vicissitudes, as developed in the Mishnah and in the Palestinian and Babylonian Talmuds. Using both a synchronic and a diachronic lens, the article shows how the scarlet ribbon is utilized in the rabbis' attempts to define their own times vis-à-vis earlier times, and to grapple with pressing religious uncertainties.